Penerapan Metode AHP Pemilihan Supplier dalam Pengadaan Bahan Baku di PT XYZ - Citra Mawarni; Fahrriza Nurul Azizah (Universitas Indraprasta PGRI Jakarta, 2023)
Every company certainly has a raw material procurement system to determine the production requirements later needed when collaborating with more than one supplier. PT XYZ is engaged in manufacturing by producing bodywork for various types of vehicles. The raw materials in the production process are almost 80% iron plate. Further, the company has a problem, namely there are frequent delays in the delivery of raw materials due to mistakes in decision making when selecting a supplier and no further research carried out to determine the order of the right criteria. In this study, researchers use the method of Analytical Hierarchy Process (AHP). The purpose of this study is to minimize the occurrence of errors in the selection of supplier and to find out which supplier is appropriate in meeting the company’s raw material needs with predetermined criteria. The results obtained are the order of the best suppliers in meeting the raw material needs of PT XYZ at CV. SB of 42.72%, CV. Kin by 34.14%, and CV. BM is 23.14% while the order of supplier selection criteria is quality, price, delivery and payment.